1999
DOI: 10.1021/jo991292t
|View full text |Cite
|
Sign up to set email alerts
|

Practical Asymmetric Synthesis of an Endothelin Receptor Antagonist

Abstract: An efficient, practical, asymmetric synthesis of the endothelin receptor antagonist 1 is reported.The key pyridine-fused cyclopentane ring bearing three consecutive chiral centers was constructed by first an auxiliary induced asymmetric conjugate addition of the bottom aryllithium from 19 to an unsaturated ester 21 in high diastereoselectivity. After a highly diastereoselective addition of the top aryl Grignard reagent to the aldehyde 22, the alcohol product then underwent a stereospecific intramolecular alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Catalysts 21 were prepared in good to excellent yields from Cbz-or Fmoc-Lproline or Cbz-4-hydroxy-L-proline and the corresponding commercially available chiral amines and β-amino alcohols through the reaction sequence shown in Scheme 3. β-Amino alcohols employed in the preparation of catalysts 21i [35] and 21n [36] were synthesized according to literature procedures from (1S,2R)-cis-1-amino-2-indanol and (1R,E)-camphorquinone-3-oxime, respectively. Very recently, Córdova has demonstrated that simple amides derived from primary amino acids such as alanine (see 10 in Scheme 1) efficiently catalyze the direct enantioselective addition of ketones to nitrostyrenes.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts 21 were prepared in good to excellent yields from Cbz-or Fmoc-Lproline or Cbz-4-hydroxy-L-proline and the corresponding commercially available chiral amines and β-amino alcohols through the reaction sequence shown in Scheme 3. β-Amino alcohols employed in the preparation of catalysts 21i [35] and 21n [36] were synthesized according to literature procedures from (1S,2R)-cis-1-amino-2-indanol and (1R,E)-camphorquinone-3-oxime, respectively. Very recently, Córdova has demonstrated that simple amides derived from primary amino acids such as alanine (see 10 in Scheme 1) efficiently catalyze the direct enantioselective addition of ketones to nitrostyrenes.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts 21 were prepared in good to excellent yields from Cbz-or Fmoc-Lproline or Cbz-4-hydroxy-L-proline and the corresponding commercially available chiral amines and β-amino alcohols through the reaction sequence shown in Scheme 3. β-Amino alcohols employed in the preparation of catalysts 21i [35] and 21n [36] were synthesized according to literature procedures from (1S,2R)-cis-1-amino-2-indanol and (1R,E)-camphorquinone-3-oxime, respectively. Very recently, Córdova has demonstrated that simple amides derived from primary amino acids such as alanine (see nitrostyrenes.…”
Section: Resultsmentioning
confidence: 99%
“…Many naturally occurring as well as synthetic compounds containing the pyridine scaffold exhibit interesting pharmacological properties [6][7][8][9][10]. Furthermore, pyridine is one of the most popular N-heteroaromatics incorporated into the structure of many pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%